FASIES DAN LINGKUNGAN PENGENDAPAN BATUGAMPING FORMASI PARIGI DI DAERAH PANGKALAN, KARAWANG, JAWA BARAT - Fernando, Yogi; Syafri, Ildrem; Jambak, Moh. Ali (Bulletin of Scientific Contribution, 2015)
Facies and depositional environments were studied to determine the growth of the carbonate rocks of Parigi Formation in Pangkalan District, Karawang, West Java. The study was conducted at nine outcrops to identify the characteristics of the macroscopic observations. Some thin section of limestone sample was taken at each location of the observations used to make microscopic analysis. Macroscopic and microscopic analysis of twenty one rock sample classified into six facies, namely: coral bafflestone facies, coral bindstone facies, algae - foraminifera packstone facies, foraminifera packstone facies, interbedded wackestone – grainstone facies, and mudstone facies. A composite log created on the outcrops around G.Guha to determine the stratigraphic of Parigi Formation in Pangkalan District. Facies succession in the composite log grouping facies into several depositional facies associations, namely: fore reef facies, offreef slope facies, reef front facies, and reef flat facies. Depositional environments are fore reef and core reef.